Avaliação da aceitabilidade do sistema construtivo “Wood Frame” - Oliveira, Luciana Albino de (2014)
The handmade building system current in the country has long being discussed for its inefficiency and unsustainability, since it employs a great deal of energy resources to construct low quality buildings and with a big waste generation. On the other hand, the search for sustainable development has been a constant in all sectors of the economy. In this context, the industrialization of construction presents itself as a viable solution, once the processes are optimized, waste is reduced and quality is assured by the supplier of the technology. Among the industrialized building systems, Wood Frame stands out for its high thermal and acoustic performance, in addition to the possibility of using a material easily renewable and environmentally friendly. But, in Brazil, the system still occupies a shy position in the construction industry. The aim of this study is to investigate the measure of acceptance of Wood Frame building system by architects and users in the cities of Curitiba (PR) and São Bento do Sul (SC), as well as the reasons for the positioning adopted: identify the knowledge of this system; identify through which media they learned about the model; identify the system specification by architects and the use of it by consumers; and, in the negative, identify what would make them change positions. The method used was a research conducted through questionnaires applied to architects and also with users. Supplementing the study, a theoretical framework demonstrates the potential of this technology. The obtained results have shown that the vast majority of professionals does not specify the system due to lack of full knowledge of the method or by lack of contact with supplier companies; while the user generally doesn’t consider it as first choice for the same reasons described above. Remains demonstrated that the studied system has potential and advantages, and needs greater disclosure to improve their performance in the construction industry.